A Novel Sulfonamidoglycosylation of Glycals - Colinas, Pedro Alfonso (2003)
The sulfonamidoglycosylation of benzylated glycals using a catalytic amount of triphenylphosphine hydrobromide proceeded in a highly stereoselective fashion to give the β anomers with good to high yields. This process was demonstrated with D-galactal and D-glucal. Two of the new N-2-(deoxyglycosyl)sulfonamides were tested as inhibitors of tumor cell growth in vitro and showed antiproliferative properties in the micromolar range.